Analisis Keterampilan Pengambilan Keputusan Siswa Kelas XI SMAN 1 Cihaurbeuti - Ari Kusnandar Maulana; Diana Rochintaniawati (ISEJ : Indonesian Science Education Journal, 2021)
This research seeks to (1) obtain an overview concerning the biology learning process, (2) obtain an overview concerning the decision-making skill level of student. This research implemented qualitative method. The research subject consisted of 11th grade student of SMAN 1 Cihaurbeuti. The sample of the research was selected through snowball sampling. The data collection technique used was non-participant. The research instrument used in the study is a decision-making skill instrument. The research results revealed that decision-making skill of students are still at the low criteria.